2017
DOI: 10.1001/jamapsychiatry.2017.3016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of Major Depression With Atypical Features and Obesity-Related Immunometabolic Dysregulations

Abstract: The phenotypic associations between atypical depressive symptoms and obesity-related traits may arise from shared pathophysiologic mechanisms in patients with MDD. Development of treatments effectively targeting immunometabolic dysregulations may benefit patients with depression and obesity, both syndromes with important disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
159
4
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(194 citation statements)
references
References 54 publications
18
159
4
2
Order By: Relevance
“…For example, MDD workgroup has been a part of the PGC since 2007, and now it covers over 100 000 people with depression. The PGC MDD group has published a paper confronting the notably challenges in genetic dissection of MDD and keeps increasing sample size and expanding their studies . The ENIGMA MDD working group includes brain scans of around >5000 MDD patients and >9000 controls from 35 research samples of 14 different countries worldwide.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, MDD workgroup has been a part of the PGC since 2007, and now it covers over 100 000 people with depression. The PGC MDD group has published a paper confronting the notably challenges in genetic dissection of MDD and keeps increasing sample size and expanding their studies . The ENIGMA MDD working group includes brain scans of around >5000 MDD patients and >9000 controls from 35 research samples of 14 different countries worldwide.…”
Section: Future Directionsmentioning
confidence: 99%
“…The aims of the current study were to identify data-driven subtypes of depressive symptoms in young people (aged [15][16][17][18][19][20][21][22][23][24][25] with MDD and to compare potential structural brain alterations between these subtypes. The data-driven symptom subtypes found in the YoDA study cohort were in line with the subtypes characterized by opposite neurovegetative symptoms previously identified in adults (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Cortical thickness increases until approximately age 2, whereas cortical surface area increases, depending on the region, until adolescence, making it more vulnerable to early life stressors (71)(72)(73)(74). In addition, cortical surface area alterations have been found to be associated with early onset depression (75,76), and prior research shows that the increased appetite, or atypical neurovegetative, subtype is associated with earlier onset of depression (13,19,24). However, since this study consisted of adolescents and young adults, the age of onset was low overall and did not differ between subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings for other cardio-metabolic traits have been inconsistent. Previous studies have identified genetic overlap between MDD and BMI using polygenic risk scores (19), but not based on genetic correlations (20). However, more recent GWAS studies now have the power to detect a genetic correlation between MDD and BMI (14).…”
Section: However It Remains Unclear To What Extend These Mechanismsmentioning
confidence: 99%